2016
DOI: 10.1213/xaa.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Migration of a Central Venous Catheter in a Hemodialysis Patient Resulted in Left Atrial Perforation and Thrombus Formation Requiring Open Heart Surgery

Abstract: Central venous catheterization is widely used in patients on hemodialysis. A rare complication associated with the clinical use of central venous catheters is perforation of the heart or major vessels. We report a case of inadvertent perforation of the left atrium and thrombosis after the placement of a hemodialysis catheter in the right internal jugular vein. In such cases, surgical removal of the central venous catheter from perforation sites in the heart and vessel walls poses anesthetic challenges because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Accidental vein perforation or injury to adjacent structures often results in catastrophic results, even death, and usually these patients were treated with embolization, spring coil or stent graft blocking, thoracoscopy, or open heart surgery. [7,913] In our study, when venous perforation was confirmed in patients 1 and 2, the catheter was maintained for 2 weeks and then adjusted under DSA guidance after the false lumen outside the catheter formed, and both patients underwent uneventful hemodialysis later. When the catheter was withdrawn immediately after venous perforation was confirmed in patient 3, massive hemorrhage and hemothorax occurred.…”
Section: Discussionmentioning
confidence: 69%
“…Accidental vein perforation or injury to adjacent structures often results in catastrophic results, even death, and usually these patients were treated with embolization, spring coil or stent graft blocking, thoracoscopy, or open heart surgery. [7,913] In our study, when venous perforation was confirmed in patients 1 and 2, the catheter was maintained for 2 weeks and then adjusted under DSA guidance after the false lumen outside the catheter formed, and both patients underwent uneventful hemodialysis later. When the catheter was withdrawn immediately after venous perforation was confirmed in patient 3, massive hemorrhage and hemothorax occurred.…”
Section: Discussionmentioning
confidence: 69%
“…Common popular treatment options are surgical repair by VATS [5][6][7] and endovascular repair, embolization, balloon tamponade, etc. [2,8,9,13].…”
Section: Discussionmentioning
confidence: 99%
“…Often, the preferred location for catheter access is the right internal jugular vein, for its straighter course into the superior vena cava and a reduced risk of malposition and thrombosis [2][3][4]. During the insertion of this catheter, a stiff dilator is used, which sometimes can lead to serious vascular injuries ultimately causing massive hemothorax, hypotension, cardiac arrest, or even death [5][6][7]. This usually happens in those patients who are on hemodialysis for a longer period of time and patients with central venous occlusive pathology (due to adhesion from repeated lines) [1,2,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Some of these complications can be fatal. [2,3] Malposition of the jugular or subclavian double-lumen central catheter is not an uncommon complication. [35] Femoral double-lumen central venous hemodialysis catheter malposition in adults is rare, [68] and most cases are acute, occurring right after the catheter insertion, but delayed malposition was found in our case.…”
Section: Discussionmentioning
confidence: 99%